Barriers and facilitators to participant adherence of dietary recommendations within comprehensive cardiac rehabilitation programmes: A systematic review - Vanzella, Lais Manata [UNESP] (2021)
Objective: To identify individual-, provider- and system/environmental-level barriers and facilitators affecting cardiac rehabilitation (CR) participants' adherence to dietary recommendations. Design: A systematic review of the medical literature was conducted. Six databases were searched from inception through March 2021: APA PsycInfo, CINAHL, Embase, Emcare, Medline and PubMed. Only those studies referring to barriers and facilitators reported by CR participants were considered. Pilot and case report studies, non-peer-reviewed literature and studies published in a language other than English, Portuguese or Spanish were excluded. Results: Data were extracted and analysed on the basis of individual-, provider- and system/environmental-level factors. Of 2083 initial citations, sixteen studies were included, with nine being qualitative and seven observational in design. From these, ten multi-level barriers and seven multi-level facilitators were identified. Dietary recommendations included developing healthy eating habits, transitioning to vegetarian-rich diets and increasing fish oil and n-3 intake. Only one study reported on all of the nutrition education programme factors recommended by the Workgroup for Intervention Development and Evaluation Research. Conclusion: To the best of our knowledge, this review is the first to summarise specific barriers and facilitators to recommendation adherence among CR participants. Few of the studies offered any conclusions regarding programme design that could facilitate improved dietary adherence practices. Future studies should aim to explore patient perspectives on the nutritional patterns and recommendations outlined in the Mediterranean Diet, the Dietary Approaches to Stop Hypertension Diet, Vegetarian or Vegan diets and the Portfolio Diet.